Sosialisasi dan Pemberian Tablet Tambah Darah (TTD) Remaja Putri SMP Muhammadiyah 3 Banyuwangi - Kustriyani, Anung; Deviani, Dita Amanda; Prasasti, Azmi (Journal of Health Innovation and Community Services, 2023)
Anemia is a condition that can cause disturbances in young women. Young women can experience anemia due to menstruation. To prevent anemia in young women is consumption of Blood Supplement Tablets. The Government's recommended Blood Supplement tablets contain 60 mg of iron and 0.4 mg of folic acid. Consumption of Iron Blood Tablets regularly once a week for 52 weeks. Purpose To provide knowledge and provision and assistance in taking Blood Supplement Tablets. Method Community service begins with conducting a preliminary survey to find out the problem. Video screenings, outreach, giving and assisting in drinking blood supplement tablets were also carried out. Results All students participated enthusiastically in the activity until the end. There were several questions asked to the speaker during the discussion. Blood Supplement Tablets can be taken by all female students. Conclusion Community service activities can provide knowledge and assistance in taking Blood Supplement Tablets to all female students.